‘All Four Engines Have Failed’: A qualitative study of the health impacts, reactions and behaviours of passengers and crew onboard flight BA009 which flew through a volcanic ash cloud in 1982 - Meach R; Horwell CJ; de Terte I (Elsevier Ltd, 2025)
This study investigated the experiences, health impacts and behaviours of passengers and crew onboard British Airways flight BA009 which flew through a volcanic ash cloud from Mount Galunggung, Indonesia, in 1982. In addition to secondary data sources, including a book published by one of the passengers, 18 semi-structured interviews were completed (14 passengers, 2 flight crew and 2 cabin crew) which were video recorded and transcribed verbatim. Data were analysed using reflexive thematic analysis to examine the experiences, behaviours, and actions of those onboard, and the health impacts of exposure to volcanic emissions. Our analysis identified five key themes which explain how people onboard flight BA009 responded: 1) Responsibility, 2) Airmanship and prior knowledge of aviation, 3) Upbringing and cultural background, 4) Faith and 5) Behaviour of the crew. Our study found few physical health impacts associated with the exposure to the ‘smoke’ and, despite individual cases of distress, there was no mass panic onboard the aircraft. Our findings highlight valuable information on passenger and crew behaviour in aviation crises, the risks of volcanic ash clouds to aviation, and have practical implications for aviation disaster management, planning and communication.
Keywords: Aviation; Volcanic eruptions; Emergency behaviour; Environmental disaster; Human factors; Disaster response; Qualitative research